COMPARATIVE STUDY OF LEARNING STYLES BETWEEN HIGH AND LOW ACHIEVERS IN ENGLISH LISTENING SKILL - Maula Zulfi Humaidah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: The objectives of this study were to investigate the learning styles used by the students with high and low achievement in listening skill and reveal whether there was any significant difference between learning styles used. Non-experimental comparative research design was used with the sample of 50 English Education Department students at University of Islam Malang. The instruments used were Index of Learning Style questionnaire to identify students’ learning style and Listening TOEFL scores as the matrix of students’ listening skill achievement. The data were analysed using independent sample t-test of SPSS. In general, high achievers and low achievers were found to use almost the same learning styles in each dimension, and the results of independent sample t-test proved that there was no significant difference of learning styles between high achievers and low achievers in listening skill with significant value 0.42 (>0.05). keywords: Learning Style, Listening, Achievement